Electrochemically driven dual bipolar resistive switching in LaNiO3/SmNiO3/Nb:SrTiO3 heterostructures fabricated through selective area epitaxy. Issue 19 (5th May 2022) - Zhang, Yong; Liu, Ming; Ma, Chunrui; Lu, Lu; Han, Chuan Yu
Abstract : The coexistence of two stable BRS modes with opposite polarity is observed within the same micro-sized epitaxial LaNiO3 /SmNiO3 /NSTO heterostructure cell fabricated through selective area epitaxy. Abstract : The concentration and distribution of oxygen vacancies in oxide materials not only lead to emergent phenomena, such as the enormous electrical resistance variation in perovskite nickelates, but also dominate the performance of related resistive random access memories. Therefore, it is very important to control oxygen vacancies in oxide materials at widely different levels of concentration. Here we report a strategy to realize oxygen vacancy doping via constructing a LaNiO3 /SmNiO3 interface diode working with redistribution of oxygen ions across the heterointerface driven by an electrical field. The doping effect can not only affect the electrical conductivity in the SmNiO3 film layer, but also modify the interface properties of the SmNiO3 /Nb:SrTiO3 heterostructure, leading to important enhancement of switching characteristics. Two bipolar resistive switching (BRS) modes with opposite polarity and different electrical characteristics are found to coexist in the same epitaxial LaNiO3 /SmNiO3 /Nb:SrTiO3 heterostructure fabricated through selective area epitaxy. The dual BRS phenomena can be explained by the electrochemical migration of the oxygen vacancies and oxygen ion redistribution process. Our finding suggests that the interfacial oxygen vacancy doping is an effective method to enhance the resistive switching in a nickelate-based electronic device, showing high potential for non-volatile memory applications.